Contexto geológico e história deformacional do granito Indiavaí - SW do Cráton Amazônico - Silva, Danielle Cristine da (2016)
The Indiavaí Granite is located north of the city of Indiavaí in the southwestern state of Mato Grosso. It presents irregular shape with batholiths dimensions and is characterized in that the sienogranitics and subordinately monzogranitic composition, medium to coarse grain size, equigranular to porfiritic inequigranular texture and in some casesrapakivi texture. It presente index colorleucocratic, essentially consists of quartz, alkali feldspar, plagioclase, having as amphibole and biotite mafic minerals. Based on grain size difference were distinguished two facies of this body: Medium-grained facies and Coarse- grained facies. The coarse-grained facies has the same characteristics of medium- grained facies, differentiating the grain size of essential minerals that can reach 1,0 cm the highest percentage of mafic minerals that can reach 20% hornblende and 10% biotite. From the geological mapping was established that Indiavaí granite presente intrusive character on the Alto Jauru Group rocks and it is in temporal unconformity with the Jauru Formation rock s. Three deformation phases were identified that affect this granitic body, two of ductile behavior ando ne of brittle behavior. The first phase (D1) is represented by penetrative foliation classified as schistosity (S1) and shear zones of ductile - brittle character. The second phase (D2) is characterized by a crenulation cleavage with folds tight and the third phase (D3) is represented by a series of fractures and quartz veins. The Rica and Cristo Rei shear zones are characterized by irregular thickness band that vary of tens of hundreds of meters mark ed by rocks mylonitic series: protomylonite, mylonite e ultramylonite. Both have a peculiarity the “xistonite” that are very simple paragenesis rocks, composed essentially of quartz and phyllosilicates (muscovite), from granite deformation. The principal tool used, to do the characterization of these shearzones, was the petrographic analysis, microstructural features analysis and britlle and ductile textures analysis preserved in minerals together with kinematics indicators analysis. Based these factors, it was estimated that the deformation and metamorphic temperature was between 400°C ~600°C, vary between green schist facies and amphibolite facies, witch normal k inematic moviment, where all the deformed rocks from the same protolith, the Indiavaí Granite.